Opinions of Physicians Working in Intensive Care on Telemedicine and Tele-intensive Care - Ebru Karakoç; İlkay Ceylan (Türk Yoğun Bakim Derneği Dergisi, 2022)
Objective: The use of tele-intensive care unit (ICU), which is a part of telemedicine, is recommended by the Republic of Turkey Ministry of Health in our country. In this study, we obtained information about the opinion, the level of knowledge and obstacles to the use of telemedicine and tele-ICU by physicians working in the ICU. Materials and Methods: After getting the approval of the ethics committee, the questionnaire consisting of 3 sections and 44 questions created with Google Forms was sent via the social messaging platform. Results: One hundred forty seven physicians working in the intensive care unit participated in the survey. Half of the them stated that they do not use telemedicine in the ICU. Only 5% of the participants stated that they agreed that telemedicine has a legal basis, and 83.7% stated that training should be provided for its use. Conclusion: With the preparation of the legal grounds and adequate training support, an increase in the use of telemedicine in the ICU can be expected.